Developing Eastern Johor : the Pengerang Integrated Petroleum Complex - Rahman, Serina (Trends in Southeast Aisa, 2018)
The Pengerang Integrated Petroleum Complex (PIPC) is a huge development that has emerged on the east coast of Johor. Comprising Petronas' largest refinery facility and numerous ancillary and supporting industrial areas, it is pegged to diversify Malaysia's petrochemical industry and reap the benefits of the area's fortunate position on international maritime trade routes. While initial responses to the PIPC development were of concern for Singapore's oil and gas business, the island-nation's long reputation and position in the industry means that the PIPC has some steep learning curves to traverse before coming on par with its southerly neighbour. However, the PIPC is likely to provide a solution to Singapore's limitations in terms of costly services and limited land space. It may also rejuvenate an industry now seen by some SMEs to be somewhat stagnant. While there are myriad global trends that may inhibit the complete success of the PIPC, it seems to be well placed to provide economic spillover benefits for Johor and Malaysia. Even if it does not become a top regional player, it will be able to meet local demands for Euro 5 quality products. The PIPC received a boost with Saudi Aramco's commitment to invest in the Refinery and Petrochemical Integrated Development (RAPID) project. More investments may come on board when the refinery begins operations in 2019. A full assessment of PIPC's success or failure can be conducted once other announced developments are completed and full operations begin.